2015
DOI: 10.1080/19420862.2015.1016695
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies specific to human Δ42PD1: A novel immunoregulator potentially involved in HIV-1 and tumor pathogenesis

Abstract: (2015) Monoclonal antibodies specific to human ∆42PD1: A novel immunoregulator potentially involved in HIV-1 and tumor pathogenesis, mAbs, 7:3, 620-629, DOI: 10.1080DOI: 10. /19420862.2015 To link to this article: https://doi.org/10. 1080/19420862.2015 We recently reported the identification of D42PD1, a novel alternatively spliced isoform of human PD1 that induces the production of pro-inflammatory cytokines from human peripheral blood mononuclear cells and enhances HIVspecific CD8C T cell immunity in mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Monocyte isolation, differentiation, and polarization of macrophages. Monocytes were purified from peripheral blood mononuclear cells obtained from blood buffy coats (provided by Red Cross, Hong Kong, China) or monkey peripheral blood, as we previously described (52). Monkey peripheral blood was obtained in heparinized vacutainer collection tubes from healthy female rhesus monkeys.…”
Section: Methodsmentioning
confidence: 99%
“…Monocyte isolation, differentiation, and polarization of macrophages. Monocytes were purified from peripheral blood mononuclear cells obtained from blood buffy coats (provided by Red Cross, Hong Kong, China) or monkey peripheral blood, as we previously described (52). Monkey peripheral blood was obtained in heparinized vacutainer collection tubes from healthy female rhesus monkeys.…”
Section: Methodsmentioning
confidence: 99%
“…These findings indicated that to improve the efficacy of ICB, targeting combinational mechanisms underlying HCC resistance to checkpoint inhibitors is essential for precision treatment. Notably, because Δ42PD-1 cross-reacts neither with PD-1 ligands nor with PD-1 antibodies,17 18 Δ42PD-1 confers a previously unrecognised mechanism of HCC resistance to ICB. We now provide evidence that PD-1 ICB even enhances Δ42PD-1 expression in T cells, which sustains tumourigenicity and likely accounts for one type of the acquired resistance to ICB in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that ∆42PD-1 contains an in-frame deletion of 14-amino acids within the exon 2 of PD-1 and does not interact with PD-L1/L2 17. Furthermore, while most commercially available anti-PD-1 monoclonal antibodies (mAbs) do not recognise ∆42PD-1, two ∆42PD-1-specific mAbs, namely CH101 and CH34, also do not cross-react with PD-1 18. These findings implicated that ICB targeting at PD-1 and PD-L1 will unlikely be useful for treating ∆42PD-1-mediated disease.…”
Section: Introductionmentioning
confidence: 99%
“…Six to eight weeks old female BALB/c mice (Guangdong Medical Laboratory Animal Center) and TLR4 knockout C57BL/6 mice generated using CRISPR/Cas9 technique (Cyagen Biosciences) were bred under standard pathogen-free conditions. For DNA vaccination, each mouse was immunized with 20 μg of endotoxin-free DNA vaccines or pVAX1 vector twice at four-week intervals intramuscularly plus electroporation as we described previously [ 13 ]. Two weeks after the last immunization, mice were euthanized for immunogenicity analysis.…”
Section: Methodsmentioning
confidence: 99%